Analysis of the transport flows service time of the veidcles and the assessment of the ideterminancy of external impact - Jarašūnienė, Aldona (Transport, 2003)
To increase the attraction of Lithuania as a transit country striving to promote carriers' border crossing activities and facilitate customs clearance procedures as well as freight delivery to clients it is necessary to identify the main obstacles, to analyse them and to select adequate measures and means for their elimination. Therefore, on the basis of the analysis of the transport flows service time, as well as basing on the assessment of indeterminacy of external impacts, it would be possible to deduce the main causes of idle time of transport means at customs, to estimate the dependence of service time in proportion to transport flows. Basing on theoretical estimation in this article the estimation of service time of international transport and the management of transport flows are described.First Published Online: 19 Dec 2011